Relationship between attitudes and perception toward tax administrations, government expenditure and tax complexity: theory of planned behavior - Palil, Mohd Rizal; Mohd Sakri, Salwan; Turmin, Siti Zaidah (Zes Rokman Resources, 2020)
This study aims to assess individual tax compliance using theory of planned behavior introduced by Icek Ajzen in 1985. Through this model, the study looks at the direct relationship between tax compliance behavior intention and attitude against the behavior. This study also examines how external variables such as perceptions of tax administrators, perceptions of government spending, and complexity of the tax system can directly influence the tax compliance behavior intention of taxpayers around Klang Valley. The study adopted a survey method by using a questionnaire. A total of 120 taxpayers dealing with the Inland Revenue Board around Klang Valley, namely, the Great Taxpayers, Jalan Duta, Wangsa Maju, Kuala Lumpur Bandar, Cheras, Petaling Jaya, Shah Alam, and Klang Branches, were randomly selected to be respondents. Descriptive analysis, correlation analysis, and multiple regression analysis were used to show the relationship between all variables. Results suggest that perceptions of tax administrators can influence tax compliance behavior intention. This study concludes that individuals’ tax compliance behavior intention can be predicted from their attitude toward the behavior that directly affects the intention.